Clinical and laboratory evaluation in horses submitted to intracecal fluid therapy administered in two different rates - Ventura Lopes Carvalho, Brenda; Neves de Souza, Maria Carolina; Souza Moreira, Nadyne; Parisi Marliere, Julia; Mesquita Mota, João Victor; Drumond Bento, Lucas; de Castro Benitez, Anaïs; Avanza, Marcel Ferreira Bastos; Bertoni Cavalcanti Teixeira, Raffaella; Barboza Silva, José Ricardo; Viana, Rinaldo Batista; Moura Monteiro, Bruno; et al. (Frontiers in Veterinary Science, 2026)
IntroductionTwo routes of administration for electrolyte solutions are commonly used in horses with fluid, electrolyte, and acid–base imbalances: intravenous and nasogastric. Despite the frequent use of these routes, there are situations in which they cannot be applied. In such cases, intracecal fluid therapy represents a viable alternative, as this route enables the administration of enteral electrolyte solutions even in animals lacking normal anterior gastrointestinal function. This study aimed to evaluate the effects of a neutral hypotonic enteral electrolyte solution administered intracecally at two different infusion rates in horses experimentally subjected to a 24-h fasting period.MethodsThis study employed a crossover design in which six experimentally dehydrated horses underwent two treatments: Treat10 (10 mL kg−1 h−1) and Treat15 (15 mL kg−1 h−1) with a single neutral solution. Horses were subjected to cecal cannulation via video laparoscopy using a modified Hasson technique to insert a Foley catheter for solution administration. Samples were collected at T-24 h (baseline, at the start of the water and food deprivation phase), T0h (at the end of the deprivation phase and the beginning of the fluid therapy), T4h (4 h after the start of fluid therapy), T8h (8 h after the start of fluid therapy), T12h (twelve hours after the start of fluid therapy), and T24h (twelve hours after the end of fluid therapy). Blood gas analysis and measurements of serum osmolarity, sodium, potassium, chloride, calcium, magnesium, phosphorus, fibrinogen, urea, creatinine, total protein, lactate, and glucose concentrations were performed. Urine samples were analyzed for concentrations of urea, creatinine, sodium, potassium, chloride, calcium, magnesium, and phosphorus.ResultsDuring the fluid therapy phase in animals from both groups, a progressive decrease in serum urea and potassium concentrations was recorded. A decrease in urinary specific gravity, urea and creatinine was also detected during the same period.ConclusionIntracecal administration of electrolyte solutions at rates of 10 mL (Treat10) and 15 mL (Treat15) over 12 h was effective and safe. The electrolyte solution used did not cause significant alterations in electrolyte or acid–base balance, suggesting that its composition is appropriate.